The life of animals in Japanese art - Singer, Robert T.; Kawai, Masatomo 1941-; Ambros, Barbara 1968-; Hare, Thomas B. 1952-; Marcon, Federico 1972-; Arakawa, Masaaki 1961-; Hare, Thomas Blenman 1952- (National Gallery of Art, 2019)
A sweeping exploration of animals in Japanese art and culture across sixteen centuries. Few countries have devoted as much artistic energy to the depiction of animal life as Japan. Drawing upon the country's unique spiritual heritage, rich literary traditions, and currents in popular culture, Japanese artists have long expressed admiration for animals in sculpture, painting, lacquerwork, ceramics, metalwork, textiles, and woodblock prints. Real and fantastic creatures are meticulously and beautifully rendered, often with humor and whimsy. This beautiful book celebrates this diverse range of work, from ancient fifth-century clay sculpture to contemporary pieces. The catalog is organized into themes, including the twelve animals of the Japanese zodiac; animals in Shinto and Buddhism; animals and samurai; land animals, winged creatures, and creatures of the river and sea; and animals in works of humor and parody. Exhibition: National Gallery of Art, Washington, DC, USA (05.05.-28.07.2019) / Los Angeles County Museum of Art, USA (08.09.-08.12.2019)
Published on the occasion of the exhibition "The Life of Animals in Japanese Art" held at the National Gallery of Art, Washington, D.C., May 5-July 28, 2019, and the exhibition "Every Living Thing: Animals in Japanese Art" held at the Los Angeles County Museum of Art, Los Angeles, California, September 8-December 8, 2019
Keywords: Geschichte; Kunst; Tiere -- Motiv; Japan; Art, Japanese / Themes, motives / Exhibitions; Animals in art / Exhibitions; Animals / Symbolic aspects / Japan / Exhibitions; Animals in art; Animals / Symbolic aspects; Art, Japanese / Themes, motives; Exhibition catalogs; Essays; Portraits; Illustrated works; Ausstellungskatalog -- National Gallery of Art -- 05.05.2019-28.07.2019 -- Washington; Ausstellungskatalog -- The Japan Foundation -- Tokyo; Ausstellungskatalog -- Los Angeles County Museum of Art -- 08.09.2019-08.12.2019 -- Los Angeles; Aufsatzsammlung